Single‐Cell Genome and Transcriptome Sequencing Library Construction Using Combination of MDA and Nextera Library Prep Method. Issue 1 (4th January 2016) - Andreou, Ioanna; Korfhage, Christian; Fang, Nan
Abstract: Single‐cell analysis gives insights into the heterogeneity of neighboring cells within tissues or within cell populations and is increasing in importance in life science and medicine. Genome and transcriptome sequencing require orders of magnitude of more starting material than what is found in an individual cell. Handling such small quantities means that degradation, sample loss, and contamination can have a pronounced effect on sequence quality and robustness. Recent technical advances in amplification have helped mitigate these challenges. Single‐cell sequencing addresses studies of rare cell types, heterogeneous samples, phenotypes associated with mosaicism or variability, and microbes that cannot be cultured. Single‐cell sequencing can enable the discovery of clonal mutations, cryptic cell types, or transcriptional features that would be diluted or averaged out in bulk tissue. This unit describes the entire workflow from cells to next‐generation sequencing (NGS), including cell lysis, MDA‐based whole‐genome and whole‐transcriptome amplification, and NGS library preparation. © 2016 by John Wiley & Sons, Inc.